Adhesion‐controlled anisotropic rotational molding of multilayered ultrasoft silicone films - Kaufmann, Anke; Schlicht, Samuel; Rösel, Uta; Drummer, Dietmar (Polymer Engineering and Science, 2024)
Rotational molding allows the manufacturing of geometrically complex, hollow parts while maintaining low tool costs. While the rotational molding of thermoplastics is subject to inherent limitations regarding the wall thickness and processing of ultrasoft materials, the present paper introduces the adhesion-controlled, highly dynamic rotational molding of room-temperature curing resins, enabling the fabrication of thin, multilayered films and anisotropic, ultrasoft silicone components at rotational speeds up to 2000 min−1. The studies comprise the influence of the applied rotational speeds and the different molds. Based on scanning electron micrographs, the process is shown to allow for locally tailored part thicknesses, enabling the manufacturing of multilayered films with singular layers obtaining thicknesses below 10 μm. Relying on the control of emerging centripetal forces, the rotational speed depicts a quasi-linear influence on resulting layer thicknesses, allowing for controlling the film thickness with excellent interlayer bonding. Relying on the superposition of consecutive layers, the adhesion-controlled process allows for tailoring emerging nonlinear, ultrasoft stress–strain behaviors across a broad range of desired moduli. Conducting compression tests, increased rotational speeds are shown to reduce the part stiffness, attributed to the increased relative influence of interlayer interfaces, allowing for reproducing mechanical characteristics similarly found in ultrasoft human soft tissue.<br

Changes in Material Behavior according to the Amount of Recycled Magnetic Materials in Polymer-Bonded Magnets Based on Thermoplastics - Rösel, Uta; Drummer, Dietmar (Magnetism, 2024)
The applications of polymer-bonded magnets are increasing within drive technology mostly because of new concepts concerning the magnetic excitation of direct current (DC) or synchronous machines. To satisfy this rising demand for hard magnetic filler particles—mainly rare earth materials—in polymer-bonded magnets, a recycling strategy for thermoplastic-based bonded magnets has to be found that can be applied to polymer-bonded magnets. The most important factor for the recycling strategy is the filler material, especially when using rare earth materials, as those particles are associated with limited resources and high costs. However, thermoplastic-based bonded magnets reveal the opportunity to reuse the compound material system without separation of the filler from the matrix. Most known recycling strategies focus on sintered magnets, which leads to highly limited knowledge in terms of strategies for recycling bonded magnets. This paper illustrates the impact of different amounts of recycling material within the material system on material behavior and magnetic properties that can be achieved by taking different flow conditions and varying gating systems into account. The recycled material is generated by the mechanical reuse of shreds. We found that a supporting effect can be achieved with up to 50% recycled material in the material system, which leads to only minimal changes in the material’s behavior. Furthermore, changes in magnetic properties in terms of recycled material are affected by the gating system. To reduce the reduction in magnetic properties, the number of pin points should be as low as possible, and they should located in the middle. The filler orientation of the recycled material is minimally influenced by the outer magnetic field and, therefore, mainly follows the flow conditions. These flow conditions are likely to be affected by elastic flow proportions with increasing amounts of recycled material.<br
Keywords: hard magnetic filler; recycling strategy; polymer-bonded magnets; aging impact

Correlation between the Flow and Curing Behavior of Hard Magnetic Fillers in Thermosets and the Magnetic Properties - Rösel, Uta; Drummer, Dietmar (Magnetism, 2021)
Polymer bonded magnets based on thermoplastics are economically produced by the injection molding process for applications in sensor and drive technology. Especially the lack of orientation in the edge layer, as well as the chemical resistance and the creep behavior limit the possible implementations of thermoplastic based polymer bonded magnets. However, thermoset based polymer bonded magnets have the opportunity to expand the applications by complying with the demands of the chemical industry or pump systems through to improved chemical and thermal resistance, viscosity and creep behavior of thermosets. This paper investigates the influence of hard magnetic particles on the flow and curing behavior of highly filled thermoset compounds based on an epoxy resin. The basic understanding of the behavior of those highly filled hard magnetic thermoset systems is essential for the fabrication of polymer bonded magnets based on thermosets in the injection molding process. It is shown that several factors like the crystal structure, the particle shape and size, as well as the thermal conductivity and the adherence between filler and matrix influence the flow and curing behavior of highly filled thermoset compounds based on epoxy resin. However, these influencing factors can be applied to any filler system with respect to a high filler amount in a thermoset compound, as they are based on the material behavior of particles. Further, the impact of the flow and curing behavior on the magnetic properties of polymer bonded magnets based on thermosets is shown. With that, the correlation between material based factors and magnetic properties within thermosets are portrayed.<br
Keywords: hard magnetic filler; flow and curing behavior; highly filler thermosets; polymer bonded magnets

Correlation between the Material System and the Magnetic Properties in Thermoset-Based Multipolar Ring Magnets - Rösel, Uta; Drummer, Dietmar (Magnetism, 2023)
Multipolar bonded magnets based on thermosets offer the opportunity to expand the applications of bonded magnets with respect to an increasing chemical and thermal resistance compared to thermoplastics. To utilise this option, the correlation between the material system and the magnetic properties must be explored amongst other influencing factors. This paper investigates the magnetic properties and the orientation of thermoset- (epoxy resin and phenolic resin) based bonded ring magnets with a hard magnetic filler of strontium-ferrite-oxide. The influence of the matrix material and the filler grade on the magnetic properties is correlated with the material characterisation showing a high impact of the embedding of the fillers into the matrix on the orientation and with that the magnetic properties. Based on a network theory, it can be justified that the magnetic properties can be increased due to a phenolic resin and a high filler grade. Further, it was shown that the orientation along the sample depth is highly affected by the strength of the outer magnetic field and limited in terms of the high-tool temperature in a thermoset-based production. With that, the sample depth, which reveals a proper orientation, is restricted so far.<br
Keywords: hard magnetic filler; highly filled thermosets; polymer bonded magnets; multipolar magnets; network theory

Correlation of the Thermal Conductivity and Mechanical Properties in Hybrid Filler Systems of Thermosets - Rösel, Uta; Drummer, Dietmar (Polymers, 2025)
Thermal management reveals an increasing importance due to the changing demands in terms of the compactness and the performance of electronic devise. Polymers in general and thermosets specifically depict a low thermal conductivity, where filler systems are needed to improve performance and make polymers suitable for certain applications. So far, different influencing factors in terms of improving the thermal conductivity in thermosets, mainly through the use of single-filler systems, have been investigated in. To some extent, hybrid filler systems have been examined as well; however, the behavior itself in terms of the thermal conductivity as well as the mechanical properties is rather unknown. In terms of the applications, it is essential to understand the correlation between the thermal conductivity and the mechanical properties as this is the fundamental requirement to realize a proper dimensioning of samples in applications. Therefore, this paper investigates hybrid filler systems based on boron nitride (BN) and three different second fillers with varying ratios and in terms of both the improvement of the thermal conductivity and the mechanical properties. Copper (Cu) was shown to reach the best compromise within the hybrid materials. Furthermore, criteria of an improved thermal flow path and sufficient mechanical properties have been stated in genera
Keywords: epoxy resin; two-component fillers; thermal conductivity; mechanical properties

Einfluss von Prozessparametern auf die Eigenschaften von Rotoren - Rösel, Uta; Drummer, Dietmar (Fachtagung Leitfähige Kunststoffe des Kunststoffinstituts Lüdenscheid, 2020)

Evaluation of a Recycling Strategy for Polymer-Bonded Magnets Based on Thermosets - Rösel, Uta; Drummer, Dietmar (Recycling, 2024)
Polymer-bonded magnets are increasingly being used in terms of applications in drive technology and, more specifically, in new concepts based on reluctance motors. The increasing demand for polymer-bonded magnets, especially in the context of electromobility, is leading to a shortage of materials, mainly in terms of the finite resource neodymium–iron–boron (NdFeB). So far, the recycling strategy for polymer-bonded magnets based on thermosets is pyrolysis, which leads to either a massive reduction of the magnetic properties or a high energy requirement. Therefore, the paper investigates an alternative recycling strategy for polymer-bonded magnets based on thermosets based on the reusage of shreds. Several influencing factors such as the form of the carrier material and the temperature level were varied in order to find a suitable recycling method. It was found that the magnetic properties were reduced by at least 15% compared to the pure material. The required energy and the CO2 emission were reduced by 90% compared to the pyrolysis. Thus, the strategy of recycling polymer-bonded magnets based on thermosets by the reusage of shreds leads to improved conditions compared to pyrolysis and is, therefore, a suitable alternative.<br
Keywords: hard magnetic filler; recycling strategy; thermoset; mechanical reusage of shreds

Extension of the Application Range of Multipolar Bonded Ring Magnets by Thermosets in Comparison to Thermoplastics - Rösel, Uta; Drummer, Dietmar (Magnetism, 2023)
To expand the range of applications of multipolar bonded magnets based on a thermoplastic matrix, the chemical and thermal resistance has to be increased and the reduced orientation in the rapid solidified surface layer has to be overcome. To meet these requirements, the matrix of multipolar bonded magnets can be based on thermosets. This paper investigates in the magnetic properties, especially in the orientation of hard magnetic fillers, the pole accuracy and the mechanical properties of multipolar bonded ring magnets based on the hard magnetic filler strontium-ferrite-oxide and compares the possibilities of thermoplastic (polyamide)- and thermoset (epoxy resin, phenolic resin)-based matrices. It was shown that the magnetic potential of the thermoset-based material can only be fully used with further magnetization. However, the magnetic properties can be increased using thermoset-based compounds compared to thermoplastics in multipolar bonded ring magnets. Further, a model of the orientation and pole accuracy is found in terms of thermoset-based multipolar magnets. In addition, the change of the mechanical properties due to the different matrix systems was shown, with an increase in E-Modulus, Et, and a reduction in tensile strength, σm, and elongation at break, εm, in terms of thermosets compared to thermoplastics.<br
Keywords: hard magnetic filler; highly filled thermosets; polymer-bonded magnets; multipolar magnets

Fertigung eines Spritzgießwerkzeuges zur Herstellung von Flusssperren aus kunststoffgebundenen Dauermagneten in einem Synchron-Reluktanzmotor - Rösel, Uta; Drummer, Dietmar; Köjer, Marco (Werkstoffe in der Fertigung, 2021)

Hochgefüllte Kunststoffe: Neue Potenziale durch den Einsatz von Füllstoffen zur gezielten Eigenschaftsmodifikation - Drummer, Dietmar; Grützmacher, Constanze; Kleffel, Tobias; Lanzl, Lydia; Rösel, Uta; Roth, Benedikt; Schneider, Kevin; Tomiak, Florian; Wittmann, Lisa-Maria (Jahresmagazin Ingenieurwissenschaften, 2021)
Die Anforderungen an Kunststoffbauteile erfordern meist den Einsatz von Füll- und Verstärkungsstoffen sowie Additiven zur gezielten Modifikation des Eigenschaftsprofils. In diesem Beitrag werden aktuelle Forschungsschwerpunkte des Lehrstuhls für Kunststofftechnik (LKT) in der Verbesserung von mechanischen Eigenschaften und dem gezielten Einstellen von flammschützenden, elektrischen, dielektrischen und magnetischen Eigenschaften zur Bauteilfunktionalisierung vorgestell
Keywords: Gefüllte Systeme in der AF; Flammschutz durch synergistische Wirkstoff-Kombinationen; Mehrschichtfolienextrusion; Thermoformen; Bipolarplatte; dreidimensionale Schaumstoffbauteile im Hochfrequenzschweißverfahren; Duroplastbasierte Kunststoffgebundene Dauermagnete

Improving the integrated fabrication of insulation systems in electric drives by injection molding of thermosets due to processing conditions and slot design - Rösel, Uta; Kneidl, Maximilian; Franke, Jörg; Drummer, Dietmar (Polymers, 2023)
The expanding demand for electro mobility in general and specifically for electrified vehicles requires the expansion of electro mobility technology with respect to variations in the requirements of the process and the application. Within the stator, the electrical insulation system has a high impact on the application properties. So far, limitations, such as the identification of suitable materials for the stator insulation or high costs in the processes, have hindered the implementation of new applications. Therefore, a new technology that allows integrated fabrication via the injection molding of thermosets is founded in order to expand the applications of stators. The possibility of the integrated fabrication of insulation systems to meet the demands of the application can be improved by the processing conditions and the slot design. Within this paper, two epoxy (EP) types with different fillers are investigated to show the impact of the fabrication process in terms of different parameters; these include the holding pressure or the temperature setup, as well as the slot design and with that the flow conditions. To evaluate the improvement in the insulation system of electric drives, a single slot sample, consisting of two parallel copper wires, was used. Then, the two parameters of the average partial discharge (PD) and the partial discharge extinction voltage (PDEV), as well as the full encapsulation detected by microscopy images, were analyzed. It was shown that both characteristics (electric properties—PD and PDEV; full encapsulation) could be improved in terms of an increase in the holding pressure (up to 600 bar) or a reduction in the heating time (around 40 s), as well as the injection speed (down to 15 mm/s). Further, an improvement in the properties can be reached by increasing the space between the wires, as well as the wire and the stack, due to a higher slot depth or by implementing flow-improving grooves that have a positive effect on the flow conditions. With that, the optimization of the integrated fabrication of insulation systems in electric drives via the injection molding of thermosets was enabled with respect to the process conditions and the slot design.<br
Keywords: thermoset; injection molding; insulation system

Influence of Application Conditions on the Magnetic Properties of Recycled Polymer-Bonded Magnets Based on Thermoplastics and Ferrite-Based Fillers - Rösel, Uta; Drummer, Dietmar (Recycling, 2025)

Influence of Different Filler Systems on the Thermal Conductivity and Mechanical Properties of Thermosets - Rösel, Uta; Drummer, Dietmar (Polymers, 2024)
The changing demands in terms of the compactness and performance of electronic devices increase the role of thermal management within this application field. Because polymers and especially thermosets have a low thermal conductivity, filler systems have to be used to improve their performance and make thermosets suitable for applications. So far, several factors influencing thermal conductivity have been defined; however, the combined investigation of mechanical properties as another important value in terms of applications has not been realized. Therefore, this paper analyzes thermal conductivity based on the orientation of fillers and a contact path as well as mechanical properties in different material systems. In addition to the matrix material, the filler type and grade and the geometry and size were varied. It was shown that boron nitride provides the best values in terms of thermal conductivity after orientation along the flow path is realized. An aluminum silicate was defined as the best filler system in terms of mechanical properties. However, the boron nitride was found to reveal the greatest potential in terms of applications, since the mechanical properties are likely to be increased by the usage of finishing additives such as silan

Injection Moulding of Multipolar Polymer-Bonded Magnets into Soft Magnetic Inserts for Rotors in Reluctance Motors - Rösel, Uta; Drummer, Dietmar (Magnetism, 2021)
Due to lower magnetic properties of polymer-bonded magnets compared to sintered magnets, a complete redesign of the multipolar soft magnetic flux barriers in rotors with alignment guidelines was carried out to eliminate the frequently used rare-earth magnets, causing a new influence of the outer magnetic field on the cavity by using soft magnetic inserts. Within this new process, the main influencing factors on the magnetic flux density such as filler content, tool temperature, holding pressure and injection velocity were analysed and correlated. The studies were based on the compound of Polyamide 12 and up to a 60 vol.-% of the hard magnetic filler, strontium ferrite. Based on the study, the injection moulding of multipolar-bonded magnets into soft magnetic inserts for rotors and, in turn, into complex geometries can be optimized in terms of the orientation of the filler, the microstructure and the magnetic flux density. The investigations show no significant influence of the process parameters known from the literature such as the mass temperature Tm, which affects the magnetic flux density, as well as the orientation and the microstructure similar to tool temperature Tt, but is less efficient. The main influencing factors identified during the investigations are the tool temperature Tt, the injection velocity vin and the holding pressure ph. As known influencing factors are only based on simple geometries such as ring structures or plates, new factors were determined for complex rotor geometries.<br
Keywords: moulding compounds; magnetic flux density; optical microscopy; injection moulding; reluctance motor

Multiscale polyethylene fiber - nanocellulose fiber composites through laser fusion and bacterial in situ synthesis - Schlicht, Samuel; Wesinger, Mara; Kaufmann, Anke; Rösel, Uta; Fischer, Dagmar; Drummer, Dietmar (Conference of the Polymer Processing Society 2024, 2024)
Ultra-high molecular weight polyethylene (PE-UHMW) fibers and bacterial nanocellulose (BNC) fibers both display exceptional mechanical properties alongside the outstanding tribological properties of PE-UHMW while showing an unrestricted biocompatibility. For combining the intrinsic advantages of both materials, the present work demonstrates an approach that integrates the slurry-based laser fusion of PE- Polyvinylpyrrolidone (PE-PVP) composites and the subsequent bacterial biosynthesis of nanoscopic cellulose fibers. PE-PVP composites exhibiting a fraction of 10% of PEUHMW fibers with a mean length of 5.0 mm were obtained through the locally selective, laser-based layer-wise evaporation and subsequent sintering of aqueous suspensions, yielding long fiber composites with a water-soluble matrix. The in situ synthesis of bacterial nanocellulose exploits the gelling and dissolving of high-molecular PVP in aqueous media, promoting the dispersion of individual fibers. Through the infiltration of the PE-PVP composite with nanocellulose-forming Komagataeibacter xylinus and the subsequent bacterial synthesis of BNC, a multiscale composite of PE- UHMW fibers and BNC fibers was obtained, corroborating the infiltration of micrometer-scale PE fiber composites with nanoscale cellulose fibers, yielding a nanoporous multiscale composite. Release experiments using methylene blue confirmed the potentials of PE-BNC composites for drug delivery applications, showing a sigmoidal release similar to pure nanocellulose.<br

Possibilities in Recycling Magnetic Materials in Applications of Polymer-Bonded Magnets - Rösel, Uta; Drummer, Dietmar (Magnetism, 2022)
Polymer-bonded magnets have increased significantly in the application of drive technology, especially in terms of new concepts for the magnetic excitation of synchronous or direct current (DC) machines. To satisfy the increasing demand of hard magnetic filler particles and especially rare earth materials in polymer-bonded magnets, different strategies are possible. In addition to the reduction in products or the substitution of filler materials, the recycling of polymer-bonded magnets is possible. Different strategies have to be distinguished in terms of the target functions such as the recovery of the matrix material, the filler or both materials. In terms of polymer-bonded magnets, the filler material—especially regarding rare earth materials—is important for the recycling strategy due to the limited resource and high costs. This paper illustrates two different recycling strategies relative to the matrix system of polymer-bonded magnets. For thermoset-based magnets, a thermal strategy is portrayed which leads to similar magnetic properties in terms of the appropriated atmosphere and process management. The mechanical reusage of shreds is analyzed for thermoplastic-based magnets. The magnetic properties are reduced by about 20% and there is a change in the flow conditions and with that, an influence on the pole accuracy<br

Possibilities of Integrated Fabrication of Insulation Systems in Electric Drives by Injection Molding of Thermosets - Rösel, Uta; Kneidl, Maximilian; Drummer, Dietmar; Franke, Jörg (Polymers, 2022)
Due to the increasing demand for electro mobility and specifically for electrified vehicles, the demand for electric drive technology is expanding significantly with changing requirements in terms of the process and the application. The electrical insulation system of the stator is an essential part of the fabrication process with a high impact on the application properties. Due to limitations—for example, in terms of suitable materials for the stator insulation—a new technology of integrated fabrication by injection molding of thermosets has been founded. In this study, two epoxy (EP) types with different fillers were investigated to prove their suitability in terms of the material properties in the fabrication process and the application. A general realization of the integrated fabrication of insulation systems in electrical engineering by injection molding was proved. Further, the differences regarding the suitability of the two materials are portrayed. It was demonstrated that mainly the filler material influences the fabrication process and the properties in the application, leading to differing suitability in terms of the EP 3162 EMG within the fabrication process and in terms of XW 6640-1 within the application properties of the thermal conductivity and the thermal linear expansion. It was further shown that the filler within the material system is required to increase the thermal conductivity needed for the application. The inclusion of the filler influences the reaction kinetics and the viscosity behavior. A fabrication of the material with fillers is however still possible.<br

Prozess- und werkstoffbedingte Verarbeitungsgrenzen thermoplastisch amorpher Dünnwandbauteile - Rösel, Uta; Drummer, Dietmar (VDI Fachtagung Spritzgießen, 2025)

Rotor-integrierte Dauermagnete – Spritzguss in der Antriebstechnik - Rösel, Uta; Drummer, Dietmar (VDI Fachtagung Spritzgießen, 2023)
Keywords: Rotor; Dauermagnete; Spitzguss; Kunststofftechnik; Antriebstechnik

Simulationsgestützte Auslegung eines Spritzgießwerkzeugs zur Herstellung von kunststoffgebundenen Dauermagneten auf Duroplast Basis - Rösel, Uta; Drummer, Dietmar (Werkstoffe in der Fertigung, 2022)
Keywords: Simulation; Dauermagnete; Duroplast; Spritzguss; Spritzgießwerkzeug

The Influence of the Design and Technological Parameters of Polymer-Based Multipolar Magnets with SrFeO Hard Magnetic Filler on the Residual Magnetic Properties - Rösel, Uta; Drummer, Dietmar (Magnetism, 2024)

Understanding the Effect of Material Parameters on the Processability of Injection-Molded Thermoset-Based Bonded Magnets - Rösel, Uta; Drummer, Dietmar (Magnetism, 2022)
The applications of bonded magnets in the field of injection-molded samples can be expanded by thermoset-based polymer-bonded magnets, as thermosets provide the opportunity to comply with the demands of, for example, the chemical industry or pump systems in drive applications through to their improved chemical and thermal resistance, viscosity and creep behaviour, especially compared to thermoplastic-based magnets. This paper investigates the influence of the matrix material (epoxy resin, phenolic resin), the filler type (strontium-ferrite-oxide, neodymium-iron-boron) and the filler grade on the reaction kinetics and the viscosity. Based on the determination of the impact, the theory of the network structure is founded. The network and the cross-linked structure are essential to know, as they significantly define not only the material but also the sample behaviour. The correlation between the material system and the mechanical as well as the magnetic properties is portrayed based on the general understanding of the behaviour in terms of the reaction kinetics and the viscosity as well as the theory of the network structure. With that, a basic understanding of the correlation within the material system (matrix, filler, filler grade) and between the reaction kinetics, the network and the cross-linked structure was determined, which gives the opportunity to change the mechanical and the magnetic properties based on the analyzed impact factors and to expand the applications of bonded magnets in the field of thermoset-based ones.<br
Keywords: hard magnetic filler; highly filler thermosets; polymer-bonded magnets; viscosity